Interleukin-6-174G/C Polymorphism Contributes to Periodontitis Susceptibility: An Updated Meta-Analysis of 21 Case-Control Studies. (6th December 2016) - Zhu, Junfei; Guo, Bin; Fu, Min; Guo, Wushuang; Yuan, Yifang; Yuan, He; Zhang, Suhan; Yu, Haiyang
Abstract : Introduction . Chronic Periodontitis (CP) is suggested to be related to gene variations. Present study aims to quantitatively estimate the association between interleukin-6- (IL-6-) 174G/C polymorphism and CP susceptibility. Materials and Methods . Pubmed, Embase, and Web of Science were searched up to May 2016. The meta-analyses were performed using STATA 12.0. Results . 21 studies were yielded. Significant associations were found under heterozygote comparison and dominant model in studies fulfilling HWE (GC versus GG: OR = 0.690, 95% CI = 0.560–0.849, P = 0.000 ; CC + GC versus GG: OR = 0.690, 95% CI = 0.568–0.838, P < 0.001 ); significant associations were found under heterozygote comparison and dominant model in Caucasian studies fulfilling HWE (GC versus GG: OR = 0.752, 95% CI = 0.577–0.980, P = 0.035 ; CC + GC versus GG: OR = 0.737, 95% CI = 0.576–0.944, P = 0.016 ); significant associations were found under allele comparison, heterozygote comparison, and dominant model in Brazilian population (C versus G: OR = 0.648, 95% CI = 0.497–0.845, P = 0.001 ; GC versus GG: OR = 0.621, 95% CI = 0.441–0.876, P = 0.007 ; CC + GC versus GG: OR = 0.649, 95% CI = 0.470–0.896, P = 0.009 ). Conclusion . IL-6 174 polymorphism is associated with CP susceptibility. In Brazilian and Caucasian population, IL-6 174 GG genotype plays as a risk factor to CP.